The transmission mechanisms of international business cycles: Output spillovers through trade and financial linkages - Falk Bräuning; Viacheslav Sheremirov (Federal Reserve Bank of Boston, 2021)
We study the transmission channels through which shocks affect the global economy and the crosscountry comovement of real economic activity. For this purpose, we collect detailed data on international trade and financial linkages as well as domestic macro and financial variables for a large set of countries. We document significant international output comovement following U.S. monetary shocks, and find that openness to international trade matters more than financial openness in explaining cross-country spillovers. In particular, output in countries with a high share of exports and imports responds to U.S. monetary shocks significantly more than output in countries with a low share, whereas we do not find material heterogeneity depending on international investment positions or financial flows in the balance of payments. We further document strong network amplification associated with the patterns of bilateral trade flows, as indirect spillovers account for nearly half of the total effect. Studies that do not account for direct bilateral linkages between national economies - and the indirect linkages through the network they form - may thus present an incomplete view of international business cycles.
Keywords: E52; F42; F44; G15; 330; financial linkages; international spillovers; monetary shocks; trade networks